Identification of Environmental Health and Safety in Pasar Rakyat Kertha, Kesiman Kertalangu Village, Denpasar City - Dwi Susanti Ida Ayu Made; Luh Putu Kirana Pratiwi (Warmadewa University Press, 2021)
A market is a place where sellers and buyers meet in buying and selling transactions. People's market is a traditional market. The people's market is one of the most obvious indicators of the economic activities of the people in an area. The implementation of safety and health in the work environment is not only intended for visitors but also employees (market managers), suppliers, and traders. This is because people's markets can be the main route for the spread of infectious disease outbreaks. People's markets have an important position to provide safe food. Public markets are influenced by the existence of upstream producers (suppliers of fresh ingredients), suppliers, vendors, consumers, managers, health-related officers, and community leaders. The healthy market is one of the structures in the development of the people's market.